A comprehensive guide to the management of anaemia. Issue 8 (19th April 2015) - Smith, Alastair
<x xml:space="preserve">Abstract</x> A systematic approach to evaluation and investigation is key to the successful management of anaemia. Our drug review considers the various oral and parenteral treatments available.